Radikalisme Islam dalam Sejarah Indonesia Modern - Muhammad, Afif (TAJDID, 2017)
This article analyzes the roots of Islamic radicalism in modern Indonesian history. Radical Islam which is a new phenomenon that emerged in the 21st century, his form is also visible in Indonesia. Some of the factors that led to the rise of radical Islam include normative-ideological understanding of Islam, the rapid development of capitalism and secularism, Western hegemony, and prolonged conflicts in the Middle East, social injustice, unjust and hegemonic world order. Therefore, it is important to reformulate the more inclusive and friendly method of understanding Islam, as well as engage in intercultural dialogues, so that an understanding of the pluralist characteristics can be further developed.